SOCS1 and SOCS3 as key checkpoint molecules in the immune responses associated to skin inflammation and malignant transformation - Morelli, Martina; Madonna, Stefania; Albanesi, Cristina (Frontiers in Immunology, 2024)
Suppressors of cytokine signaling (SOCS) are a family of negative inhibitors of the molecular cascades induced by cytokines, growth factors and hormones. At molecular level, SOCS proteins inhibit the kinase activity of specific sets of receptor-associated Janus Activated Kinases (JAKs), thereby suppressing the propagation of intracellular signals. Of the eight known members, SOCS1 and SOCS3 inhibit activity of JAKs mainly induced by cytokines and can play key roles in regulation of inflammatory and immune responses. SOCS1 and SOCS3 are the most well-characterized SOCS members in skin inflammatory diseases, where their inhibitory activity on cytokine activated JAKs and consequent anti-inflammatory action has been widely investigated in epidermal keratinocytes. Structurally, SOCS1 and SOCS3 share the presence of a N-terminal domain containing a kinase inhibitory region (KIR) motif able to act as a pseudo-substrate for JAK and to inhibit its activity. During the last decades, the design and employment of SOCS1 and SOCS3-derived peptides mimicking KIR domains in experimental in vitro and in vivo models of dermatoses definitively established the strong anti-inflammatory and ameliorative impact of JAK inhibition on skin inflammatory responses. Herein, we discuss the importance of the findings collected in the past on the function of SOCS1 and SOCS3 in the inflammatory responses associated to skin immune-mediated diseases and malignancies, for the development of the JAK inhibitor drugs. Among them, different JAK inhibitors have been introduced in the clinical practice for the treatment of atopic dermatitis and psoriasis, and others are being investigated for skin diseases like alopecia areata and vitiligo.Abbreviations: Leukemia inhibitory factor (LIF), Granulocyte-macrophage colony-stimulating factor (GM-CSF), Interferon-gamma (IFN-), Insulin growth factor (IGF), Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-B), Interferon regulatory factor 1 (IRF1), Tumour necrosis factor-alpha (TNF-), Phosphatidylinositol 3 kinase (PI3K), Transforming growth factor B (TGF-b), Human beta defensin-2/3 (HBD-2/3), Tyrosine kinase 2 (TYK2)